KECEMASAN IBU HAMIL DALAM MENGHADAPI PROSES PERSALINAN - Syaifurrahman Hidayat (Wiraraja Medika : Jurnal Kesehatan, 2013)
Background: TheWorld Health Organization(WHO) in 2005explainedthat theglobalmentalhealth statusshowed25% of Fiscardohave experiencedemotional andbehavioraldisorders, butonly40% arediagnosed. Anxietyoranxietyof pregnant womenwhowill faceone ofthe delivery processemotionalproblemsfrequently encountereddisordersandpsychologicalimpactis quiteserious. Astuti(2005) regardingthe factors that causeanxietypregnant women, from50obtained46% of respondentsexperiencedmildanxiety, anxietywas50%, and4% severe anxiety0bjective:To analyze thematernalanxietyin the face oflaborinOrchidVillagePolindes Anggrek Pabean Sumenep Methods:this researchisdescriptivedesignused inthis studywascross-sectional. Forprocessingthe datausingthe completed questionnairesare then processed bystagesincludingEditing, Coding, ScoringandTabulatingResults:The results showedthat most respondentsshowedanxietyin the face oflaborisas much as69.6%. WhereAnxietyliabilitypartofthe logicfunctionsthose weakenintuitionor vice versa.Anxietycaused bythe individualin the form ofmaladaptivecopingresponsesthatare destructive(destructive). Adjustmentornormalizationstressorfailedresulting intensionandimprovesconcentrationonissuesthat are considered importantConclusions: Themajority ofrespondentsareexperiencinganxietyin the face ofthe delivery processas much as69.6% and thefractionof respondentsinthe category ofmildanxietyandworrydo noteach as much as8.7%.  Keywords:Anxiety, Pregnancy, ChildbirthProcess